2017
DOI: 10.1056/nejmoa1616540
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous Wave-free Ratio versus Fractional Flow Reserve to Guide PCI

Abstract: BACKGROUNDThe instantaneous wave-free ratio (iFR) is an index used to assess the severity of coronary-artery stenosis. The index has been tested against fractional flow reserve (FFR) in small trials, and the two measures have been found to have similar diagnostic accuracy. However, studies of clinical outcomes associated with the use of iFR are lacking. We aimed to evaluate whether iFR is noninferior to FFR with respect to the rate of subsequent major adverse cardiac events. METHODSWe conducted a multicenter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
533
1
24

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 820 publications
(575 citation statements)
references
References 33 publications
17
533
1
24
Order By: Relevance
“…These results suggest that the benefits of physiologically guided coronary revascularization with FFR can also be achieved with iFR. Our principal findings are similar to those now reported in the Journal by Götberg et al 16 It has previously been proposed that a hybrid iFR-FFR approach might be advantageous for the detection of functionally significant stenoses, with iFR used as the initial measure and FFR used only to evaluate stenoses that were of intermediate severity on iFR-guided assessment. 17,18 However, the results of our trial suggest that iFR alone can effectively identify stenoses that require intervention.…”
Section: Discussionsupporting
confidence: 90%
“…These results suggest that the benefits of physiologically guided coronary revascularization with FFR can also be achieved with iFR. Our principal findings are similar to those now reported in the Journal by Götberg et al 16 It has previously been proposed that a hybrid iFR-FFR approach might be advantageous for the detection of functionally significant stenoses, with iFR used as the initial measure and FFR used only to evaluate stenoses that were of intermediate severity on iFR-guided assessment. 17,18 However, the results of our trial suggest that iFR alone can effectively identify stenoses that require intervention.…”
Section: Discussionsupporting
confidence: 90%
“…[197][198][199] Nonetheless, two randomized trials have demonstrated that a strategy using an instantaneous wave-free ratio of more than 0.89 to defer revascularization yielded noninferior outcomes to a strategy using an FFR of more than 0.8. 200,201 Assessments of MBF and Flow Reserve Quantification of MBF using PET, allowing assessment of peak hyperemic MBF as well as noninvasive calculation of MFR, is physiologically distinct from FFR. 202 Unlike FFR, MFR evaluates the effects of abnormality over the entire coronary circulation (Figure 9).…”
Section: Ffrmentioning
confidence: 99%
“…The resting indices perform similar with an overall diagnostic agreement between 80% and 90% when compared with FFR depending on distribution of lesions included in the studies 20, 21, 22, 23, 24. Still, instantaneous wave‐free ratio–based strategies versus an FFR strategy resulted in comparable clinical outcomes at 1 year in 2 large, randomized clinical trials 23, 24. We found a diagnostic accuracy for QFR (87%) comparable to the early instantaneous wave‐free ratio/FFR studies.…”
Section: Discussionmentioning
confidence: 63%